2006
DOI: 10.3347/kjp.2006.44.1.91
|View full text |Cite
|
Sign up to set email alerts
|

A case of sparganosis mimicking a varicose vein

Abstract: Recent advances in radiological and serological techniques have enabled easier preoperative diagnosis of sparganosis. However, due to scarcity of cases, sparganosis has been often regarded as a disease of other etiologic origin unless the parasite is confirmed in the lesion. We experienced a case of sparganosis mimicking a varicose vein in terms of clinical manifestations and radiological findings. Sparganosis should be included among the list of differential diagnosis with the varicose vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…3). Koo et al (8) reported that serpiginous tubular tracts were characteristic findings and we believe the unique wall shape may be helpful in differentiation. The presence of peripheral eosinophilia is also a helpful finding.…”
Section: Discussionmentioning
confidence: 69%
“…3). Koo et al (8) reported that serpiginous tubular tracts were characteristic findings and we believe the unique wall shape may be helpful in differentiation. The presence of peripheral eosinophilia is also a helpful finding.…”
Section: Discussionmentioning
confidence: 69%
“…11 There was even a reported case of intramuscular sparganosis in the lower leg the preoperatively mimicked a thrombosed varicose vein. 21 In a case of cerebral sparganosis, computed tomog-…”
Section: A B C Discussionmentioning
confidence: 99%
“…Radiological (Chung et al, 1995;Kim et al, 2005;Koo et al, 2006) and serological (Kong et al, 1994) techniques can provide useful diagnostic clues of sparganosis. However, in the case of breast sparganosis, radiological images closely resemble those of a neoplasm or granulomatous mastitis (Jeong et al, 1995;Chung et al, 1995;Moreira et al, 1997;Kim et al, 2005).…”
mentioning
confidence: 99%